1994
DOI: 10.1111/j.1600-065x.1994.tb00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Galα(1,3)Gal, the Major Xenoantigen(s) Recognised in Pigs by Human Natural Antibodies

Abstract: The transplantation of pig organs to humans (xenotransplantation) is now receiving serious consideration because of the shortage of human donors for organ transplants of kidney, liver and heart, and of islet cell transplantation for diabetes. The problem with such xenografts would be hyperacute rejection--mediated by natural antibodies in humans to pig antigens, complement fixation to endothelial cells, and the rapid onset of intravascular coagulation. It is now clear that the major target of the natural IgM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
175
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(176 citation statements)
references
References 38 publications
(36 reference statements)
1
175
0
Order By: Relevance
“…In humans, apes and Old World primates, essentially all pig-reactive antibodies recognize the carbohydrate epitope Galα1-3Galβ1-4GlcNAc-R, (αGal). 4,5 αGal-reactive antibodies bind to αGal epitopes expressed on the surface of vascular endothelial cells within pig organs and initiate activation of the complement system, which in turn induces rapid destruction of endothelial cells and loss of vascular integrity culminating in hyperacute rejection. 6 In the absence of complement, αGal-reactive antibodies cause a delayed form of graft rejection referred to as delayed xenograft rejection or acute vascular rejection.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, apes and Old World primates, essentially all pig-reactive antibodies recognize the carbohydrate epitope Galα1-3Galβ1-4GlcNAc-R, (αGal). 4,5 αGal-reactive antibodies bind to αGal epitopes expressed on the surface of vascular endothelial cells within pig organs and initiate activation of the complement system, which in turn induces rapid destruction of endothelial cells and loss of vascular integrity culminating in hyperacute rejection. 6 In the absence of complement, αGal-reactive antibodies cause a delayed form of graft rejection referred to as delayed xenograft rejection or acute vascular rejection.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the control 1 donor heart was rejected at 25 min in the recipient cynomolgus monkey with an average CH50 unit and a slightly high IgM titer. Therefore, the case of control 2, with a relatively low level of IgM and IgG titer (48), which was rejected in 165 min after transplantation, might be a rare case for the pig to cynomolgus monkey combination.…”
Section: Fig 5-continuedmentioning
confidence: 99%
“…Other recognition structures on human NK cells for porcine EC may include CD2 (62) or leukocyte integrins (65), which may be involved in the recognition of PAEC by human NK cells. It also has been suggested that human NK cells somehow recognize the ␣-galactosyl epitope expressed on pig cells (66) recognized by natural Abs and responsible for hyperacute rejection of xenografts in appropriate model systems (67)(68)(69). Although the capacity of human lymphocytes to recognize porcine MHC has been reported, this has been only for recognition by CD4 ϩ T cells that resulted in proliferation of those human T cells (70).…”
Section: Discussionmentioning
confidence: 99%